Sygeplejevidenskab - myte eller virkelighed? Om genese og struktur af feltet af akademiske uddannelser og forskning i sygepleje i Danmark - Petersen, Karin Anna (AU Library Scholarly Publishing Services, 2023)
ENGLISH SUMMARY: The aim of this study is to explore the feasibility and productivity of a model for description and analysis of what Bourdieu has called “the genesis and structure of cultural fields”, when the model is applied to the genesis and structure of a Nursing/Care Science, and of the corresponding practical, undergradutae and graduate Education for these purposes, in Denmark, during the last 20 years. The study is primarily heuristic, and covers domains like education and pedagogy, epistemology and sociology of science. The study does not pretend that there is or can be a relatively autonomous field of Nursing/Care Science and Education under constitution in Denmark, in the technical sense of Bourdieu’s field studies, since central features of the process point into contradictory directions. The study tries to disentangle the complex as much as possible. During the period the craft of nursing has increasingly become academic, claiming to be based on scientific research. Among other things this has also resulted in different tentatives to organize undergraduate and graduate studies in the field, under the umbrella of different institutions and associations for research, higher learning and practical education. The study comprehends three parts: a theoretical-empirical study of the undergraduate and postgraduate education in the field, complemented with the conclusions of a historiographic and analytical study of the institutions and associations implied in this effort to create academic-scientific structures, and two volumes of appendices, one volume related to the instruments and tables of the theoretical-empirical main study, and another volume containing the details of the historiographical study and the bibliography . 2.8.1 The three theoretical-empirical inquiries Problem, theory and method. The theoretical-empirical study starts with a presentation of the domain of problems studied, and of the theories of Bourdieu that will be applied. The first chapter makes some of the basic elements of theory and method available, with two of Bourdieu’s central contributions as sources of inspiration: field theory applied to science and to research education on one side, the analysis of the faculty of Medicine in Paris as part of a field theory applied to higher education in the book “ Homo Academicus “. Here the medical science is located to the right on the dimension of faculties at the University, that is to say among the learned disciplines that are most directly integrated with a professional and autorized responsibility for the maintenance of the societal order in terms of public health etc, and hence, with economic, social and political power outside the faculty, and with academic power within the faculty. At the difference of natural science, situated at the opposite end to the left of the dimension, since it is not integrated with the mundane order within and outside the faculty, but has its function and legitimity from critical thinking and fundamental science. To the extent that the possible science of Nursing/Care would appear constitutively bound by Medical Science, the analogy with the analysis of Medical Science may be worthwhile to explore. There is also a chapter that explains how the conceptual structure, the operationalisation and thee questionaire of Bourdieu’s Homo Academicus have been adapted for the purposes of this research.. The empirical part of the theoretical-empirical study comprehends three complementary subprojects. 2.8.2 The survey The first step is made up of a questionnaire survey directed towards the population of both students and graduates/postgraduates implied. The questionnaire is printed in the appendix-part, together with the frequency tables of answers to the majority of the questions usefull for the further study. The questionnaire aims at a description of the demographic, social and cultural background and life style of the students/researchers/lecturers, their ressources possibly relevant for the fact that they as former nurses started a second education in view of a different professional career, their position in the area of nursing and their standpoints on the actual development of nursing in terms of changes in the clinicial basic practical education and In-Service education, the creation of academic undergraduate education and postgraduate education, the organisation of research, the orientation of this whole development in terms of epistemology, paradigms of science, relation theory/practice etc. That is to say in terms of Bourdieu: their economic, social, cultural and symbolic capital, incorporated, objectified and institutional, related to their positions and positionings in the domain of their craft. There is an extensive discussion of the reasons and consequences of the low /normal percentage of return of the mailed questionaires (circa 56 % of around 400 adressees). Indirect tests are brought in, in order to appreciate the degree of representativity. The conclusion is that this part of the project has to be understood as an exploration rather than as a test of the method, although there are almost no indirect signs of systematic biases in the return-sample. The tabels with the frequencies of answers (cf. Appendices) are briefly commented, in as much they need some presentation in view of the central analysis.The whole set of data offered by the questionnaire inquiry have been submitted to an analysis of correspondences, often used by Bourdieu and scholars working in that tradition, by now well introduced in Scandinavia as well, executed with the help of the consultant Marianne Høyen.The non-mathematical aspects of the method are extensively presented, as well as 5 graphical representations together with a comment of the graphes. The figures suggest without doubt that there are elements that discriminate between different profiles among the researchers and students, as far as their capitals, positions and positionings are concerned. Even if they as yet do not appear very clear cut: their interpretation will depend on further empirical-theoretical confirmation. 2.8.3 The analysis of the dissertations The second empirical inquiry concerns only the ph.d dissertations of the researchers and the candidate dissertations of the Candidates in Cura from the independent School of Advanced Nursing Education at Aarhus University, basically a School for in-service training of nurses, but now housing even a cand. cur. education . The dissertations have been analysed in two ways. By categorizing the bibliographical references there is a possiblity to define the scientific universes that have been consulted and used in the work for the dissertations. One of the intresting findings here is that there is an obvious contradiction between the tacit or open basic claim of the field alledgedly under constitution, to represent clinical nursery science, and the bulk of philosophical, human and social science inputs that are brought into play in the dissertations, while references to medical litterature are minimal.This may have to do with the contradictions in the constitution of the cand. cur. education programme, which will be discussed in the historiographic part, and with the fact that the involved researchers, if they possess a ph.d., have obtained it from human- and social science university faculties.This happened by necessity, because there were no and there are still almost no other possiblities in Denmark at least. But it happened also in many cases as a matter of principle and preference. The text of the dissertations have been analysed and categorized, and transformed in frequency tables, which in turn also have been submitted to a correspondence analysis. Even here a system of profiles defining different conceptions of the scientific craft involved in alledged nursery/care science writing do emerge, almost too much similar to those profiles that are the eternal reminders in the debate of the last 10 years. But some more hidden configurations also appear. All these category systems and frequency tables are to be found in the appendices. The text of the historiographical and analytical presentation of the involved institutions in detail,which constitutes a second part of the study, is displaced to the second volume of appendices, because of its extension. The reader will have to consult it there, but can take part of the conclusions in the first part , as they are integrated in the general conclusion of the first theoretical-empirical part, where the historiographic part is used to confirm, illustrate and complement the results of the objectified empirical inquiry. The theoretically constructed objectified data of the first part need, at least for the reader who has not been a participant in the process, a historical description of the process, seen from the six main institutions and associations that have been housing the endeavour. At the same time it will be possible to describe other structural features of these activities.This historical reconstruction is meant to complement the first part in terms of more fully narrative and structural descriptions, which are comparable to the objectified quantifications. But it is also meant as a contribution to the social history and the history of ideas and science of the academic and scientific transformation of the craft, by a participant who is a professional on the practical and the theoretical side, but not a historian. Besides it is also to be appreciated as an effort to make available an overview of the documents and events, theoretically accessible for all interested people, but in fact almost impossible to collect, except for an insider . The environments studied are: The creation of a chair in Nursery Science at the Faculty of Medicine of Odense University The activities of the Danish Institute for Health an Nursing Research ( DISS) The activities of the Scool of Advanced Nursing Education at Aarhuus University ( DSH) The activities of the University Hospitals Center for Nursing Research in Copenhagen (UCSF) The activities of the Danish Nursing Research Society (DSS) The activities of the Society of Academic Nurses in Denmark ( FASID) Environments like the activities initiated by the Medical Research Council, or the social science Institutes of the Universities are not systematically considered in this second part . The presentations focus mainly on the following aspects: academic structure and legitimation, recruitment of personnel, research activities and research paradigms, degree, education, curriculum, scientific paradigms. This part concludes, focusing upon the differences within and between institutions, and upon the background of the tacit common ground (doxa), commonly named clinical nursing science. The general conclusion of the dissertation compares the results of the first three empirical inquiries and the historiographical part in the light of the original question, generated by the field theory: can one observe, in Denmark today, in the field of Nursing/Care, the genesis of a relative autonomous field of Nursing/Care Science? The answer defended by the study is that the mutual dependency of Medical Treatment and Nursing/Care either in principle or in fact tends to difficult the genesis of such a field, either as a fundamental theoretical science or as a scientific technology. At the same a time there is a tendency to the autonomisation of the craft which is prolongated and reinforced by a tendency to translate professionalisation into academic and scientific autonomy. But even this tendency is complicated by the contradiction between the option to subordinate clinical nursery to clinical medicine in theory and practice, and the option to constitute an autonomous field in terms of a social science of education, nursing and care.